The association between nutritional status and body image perception among Auxiliary Police in UiTM Selangor, Malaysia / Mohd Fariezzuan Harun - Harun, Mohd Fariezzuan (2016)
Body image plays an important role in determining people's satisfaction towards their physical appearance. This study examined the relationship between nutritional status and body image perception among Auxiliary Police. Body image perception among Auxiliary Police is important to be studied as they are the frontline in the university that provide a safe and healthful environment to work, live and learn in the campus. This study aims (i) to assess nutritional status consisting of anthropometric data (BMI) of Auxiliary Police in UiTM, (ii) to determine the body image perception among Auxiliary Police in UiTM, (iii) to correlate the nutritional status and body image perception of Auxiliary Police in UiTM. A total of 122 Auxiliary Police (l08 males and 14 females) aged between 20 to 60 years old from all UiTM campuses in Selangor (UiTM Shah Alam, UiTM Puncak Alam, UiTM Puncak Perdana, UiTM Sungai Buloh and UiTM Selayang) had involved in this cross sectional study. The instrument used in this study is Body Shape Questionnaire (BSQ) which is adapted from Dowson and Henderson (2001) and nutritional assessment is done by assessing their weight and height in order to obtain the BMI. All Auxiliary Police were chosen randomly. The data of this study is analysed by using Statistical Package for the Social Sciences (SPSS) Version 21 and the Body Mass Index (BMI) were categorized by using the World Health Organization (WHO, 2007). Result shows that higher percentage of 54.1% Auxiliary Police have a low level of concern regarding body image perception compared to only 45.9% of them who have a higher concern towards their body image. Apart from that, it outline that there is no significant association between age, gender and household income with body image perception with p value = 0.198, P value = 0.450, P value 0.420 respectively. However, there is a positively strong relationship between BMI and body image perception with the p value obtained is < 0.05. Therefore, intervention programmes should be done to improve the body image perception among Auxiliary Police in UiTM. Keywords: Auxiliary Police, Body Dissatisfaction, Body Mass Index, Body Image Perception, Nutritional status